PENAKSIR RASIO DAN PRODUK EKSPONENSIAL YANG EFISIEN UNTUK VARIANSI POPULASI PADA SAMPLING ACAK SEDERHANA - Mega Elysmayanti; Firdaus '; Haposan Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Estimators discussed here are three estimators for estimating population variance in simple random sampling without replacement, i.e. exponential ratio estimator using variance of auxiliary variable, and exponential ratio and product estimators using mean of auxiliary variable. This work is a review of article written by Asghar et al. [Revista Colombiana de Estadistica, 37 (2014): 213-224]. These estimators are all biased and mean square error (MSE) of each estimator can be obtained. Furthermore, these MSE are compared to each other. The most efficient estimator is the one which has the smallest MSE. An example is given to show the efficiency of the estimator.